Unrestricted modification search reveals lysine methylation as major modification induced by tissue formalin fixation and paraffin embedding. Issue 15 (3rd May 2015) - Zhang, Ying; Muller, Markus; Xu, Bo; Yoshida, Yutaka; Horlacher, Oliver; Nikitin, Frederic; Garessus, Samuel; Magdeldin, Sameh; Kinoshita, Naohiko; Fujinaka, Hidehiko; Yaoita, Eishin; Hasegawa, Miki; et al.
<x xml:space="preserve">Abstract</x> Formalin‐fixed paraffin‐embedded (FFPE) tissue is considered as an appropriate alternative to frozen/fresh tissue for proteomic analysis. Here we study formalin‐induced alternations on a proteome‐wide level. We compared LC‐MS/MS data of FFPE and frozen human kidney tissues by two methods. First, clustering analysis revealed that the biological variation is higher than the variation introduced by the two sample processing techniques and clusters formed in accordance with the biological tissue origin and not with the sample preservation method. Second, we combined open modification search and spectral counting to find modifications that are more abundant in FFPE samples compared to frozen samples. This analysis revealed lysine methylation (+14 Da) as the most frequent modification induced by FFPE preservation. We also detected a slight increase in methylene (+12 Da) and methylol (+30 Da) adducts as well as a putative modification of +58 Da, but they contribute less to the overall modification count. Subsequent SEQUEST analysis and X!Tandem searches of different datasets confirmed these trends. However, the modifications due to FFPE sample processing are a minor disturbance affecting 2–6% of all peptide‐spectrum matches and the peptides lists identified in FFPE and frozen tissues are still highly similar.